2021
DOI: 10.15561/26649837.2021.0401
|View full text |Cite
|
Sign up to set email alerts
|

Physiological impact of wearing a surgical face mask during walking in the COVID-19 pandemic

Abstract: Background and Study Aim. Common use of surgical face masks is recommended for social and individual health due to the COVID-19 pandemic. However, there is no systematic report for responses of organism to wearing a surgical face mask during different exercises. In this context the purpose of this study was to examine the impacts of wearing a surgical face mask during a one-hour brisk walking. Material and Methods. A total of thirty male (n=16) and female (n=14) volunteers (mean age and BMI of 32±1.07 ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Overall, 22 studies used a progressive exercise test [ 3 , 12 , 14 , 18 , 24 , 26 , 30 , 35 , 36 , 39 , 41 , 43 – 45 , 48 , 50 , 51 , 53 – 55 , 59 , 60 ], while 19 employed the steady-state constant exercise test [ 13 , 15 , 25 , 29 , 31 , 34 , 37 , 38 , 40 , 42 , 46 , 47 , 49 , 52 , 56 58 , 61 , 62 ], and two used interval exercise tests [ 28 , 32 ]. Moreover, one study used a resistance exercise test [ 33 ], and one used a sit-to-stand test [ 27 ].…”
Section: Resultsmentioning
confidence: 99%
“…Overall, 22 studies used a progressive exercise test [ 3 , 12 , 14 , 18 , 24 , 26 , 30 , 35 , 36 , 39 , 41 , 43 – 45 , 48 , 50 , 51 , 53 – 55 , 59 , 60 ], while 19 employed the steady-state constant exercise test [ 13 , 15 , 25 , 29 , 31 , 34 , 37 , 38 , 40 , 42 , 46 , 47 , 49 , 52 , 56 58 , 61 , 62 ], and two used interval exercise tests [ 28 , 32 ]. Moreover, one study used a resistance exercise test [ 33 ], and one used a sit-to-stand test [ 27 ].…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have shown that N95 masks reduce the oxygen concentration of blood by more than 20 -25%. Therefore, it is vital to thoroughly assess the risk factors of wearing facemasks for long durations (15,16). It is also vital to have further studies to find an alternative for surgeons who frequently have long procedures in operation rooms.…”
Section: Discussionmentioning
confidence: 99%
“…Rosner et al (23) also stated that the problems of using masks in HCW requires further research. There are some other studies that they have investigated the effect of using a mask on the cardiopulmonary system (24,25).…”
Section: Discussionmentioning
confidence: 99%